Hypertrophic effect of inhaled beta2‐agonist with and without concurrent exercise training: A randomized controlled trial. (7th June 2018) - Jessen, S.; Onslev, J.; Lemminger, A.; Backer, V.; Bangsbo, J.; Hostrup, M.
Abstract : Due to a high prevalence of asthma and exercise‐induced bronchoconstriction in elite athletes, there is a high use of beta2 ‐adrenoceptor agonists (beta2 ‐agonists) in the athletic population. While anabolic in rodents, no study has been able to detect hypertrophy in humans after chronic beta2 ‐agonist inhalation. We investigated whether inhaled beta2 ‐agonist, terbutaline, alters body composition and metabolic rate with and without concurrent exercise training in healthy young men. Sixty‐seven participants completed a 4‐week intervention of daily terbutaline (8 × 0.5 mg) or placebo treatment without concurrent training (habitual; n = 23), with resistance (n = 23) or endurance (n = 21) training 3 times weekly. Before and after the interventions, participant's body composition was determined by dual‐energy X‐ray absorptiometry and resting metabolic rate and substrate oxidation by indirect calorimetry. Terbutaline increased lean body mass by 1.03 kg (95% CI 0.29‐1.76; P  < .05) and 1.04 kg (95% CI 0.16‐1.93; P  < .05) compared to placebo in the habitual and resistance training group, respectively, but had no effect compared to placebo in the endurance training group [−0.56 kg (95% CI −1.74‐0.62; P  > .05)]. Fat mass, bone mineral content, and resting metabolic rate did not change differently between treatments with the intervention. Daily inhalation of terbutaline in near‐therapeutic doses induces skeletal muscle growth. This observation should be a concern for antidoping authorities.